Malpaso” Stream: Identification of Social and Environmental Conflicts Through Social Mapping in Medellín - Camargo Castro, Diego Alejandro (2023)
The environmental conflicts in the water sub-basins that irrigate Medellín and the Aburrá Valley have generated numerous social problems, altering the territorial dynamics of neighborhoods and entire communities. This paper presents the situation of the Malpaso stream and the socio-environmental problems that occur there. This finding was obtained after applying social cartography as a data collection technique of the proposed methodology, considered a relevant technique for a participatory exercise like the one presented here. As an exercise of collective knowledge construction and exchange of expertise between the population and the researcher, the main sites within the Bello Horizonte neighborhood, belonging to the Robledo district of the city of Medellín, were identified. These sites require urgent community management to design programs and projects that reduce pollution and waste discharge into the Malpaso stream, and thus prevent channel interruptions and floods that affect the residents of the neighborhood.